Audit and exit: a decade of research on internal auditor turnover through a bibliometric lens - Ahmad @ Muhammad, Norizam; Mohd Noor, Azura; Malek @ Malik, Masturah; Mohd Rodzi, Nor Kartini (Universiti Teknologi MARA, Perlis, 2025)
This study examines the evolution of scholarly research on internal audit tenure and auditor turnover using bibliometric analysis. Publications indexed in the Web of Science database from 2005 to 2024 were analysed to identify trends in publication year, top authors and institutions, and dominant research areas. The analysis highlights increasing academic interest in topics related to auditor independence, audit quality, and governance. The study provides insights into the intellectual structure of the field and uncovers emerging themes and research gaps. However, a key limitation lies in the restricted use of keywords during the literature search, which may have limited the breadth and inclusivity of the reviewed literature. To address this, future research is encouraged to adopt advanced bibliometric tools such as VOSviewer to perform keyword co-occurrence and network analysis. This approach would enable a more comprehensive mapping of literature and enhance the robustness of future bibliometric studies in auditing and human capital research.